Atypical presentation in Sézary syndrome with leonine face during flu syndrome by COVID-19 (Research, Society and Development, 2021)
Cutaneous T-cell lymphomas (LCCT) comprise a heterogeneous group of Non-Hodgkin's Lymphomas that commonly present as mycosis fungoides, of indolent course, and a leukemic form, with more aggressive evolution, known as Sézary syndrome. These neoplasms make the individual more susceptible to infections resulting from immunosuppression. In March 2020, the pandemic broke out due to the new coronavirus (COVID-19), which quickly spread and caused numerous deaths. The present study describes a case of difficult diagnosis represented erythematous-desquamative lesions in the trunk and limbs, associated with intense itching in course for eight months, conducted until then as pharmacoderma, which evolved during hospitalization, after viral infection by COVID-19 intra- hospital, with infiltration in the face, thinning of eyebrows and hair, disfiguring the patient, similar to the leonine face. The patient had a flu-like syndrome due to the new coronavirus, remaining in respiratory isolation for fourteen days, progressing without serious complications and then being referred to a specialized cancer service.